Thermodynamic reassessment of the Mn-Ni-Si system - Hu B.; Du Y.; Yuan J.J.; Liu Z.F.; Wang Q.P. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Iased on the new experimental data available in the literature, the Mn-Ni-Si system has been reassessed using the CALPHAD (CALculation of PHAse Diagram) approach. Compared with the previous modeling, the τ8 and τ12 ternary phases were treated as the same phase according to the new experimental data. The Mn3Si phase was described with two sublattice model (Mn, Ni)3(Si)1. The reported new ternary phase τ was not considered in the present work. Comprehensive comparisons between the calculated and measured phase diagrams showed that a set of thermodynamic parameters of the Mn-Ni-Si system obtained in this work was more accurate than the previous one.